2020
DOI: 10.3390/jof6040344
|View full text |Cite
|
Sign up to set email alerts
|

Hex1, the Major Component of Woronin Bodies, Is Required for Normal Development, Pathogenicity, and Stress Response in the Plant Pathogenic Fungus Verticillium dahliae

Abstract: Woronin bodies are membrane-bound organelles of filamentous ascomycetes that mediate hyphal compartmentalization by plugging septal pores upon hyphal damage. Their major component is the peroxisomal protein Hex1, which has also been implicated in additional cellular processes in fungi. Here, we analyzed the Hex1 homolog of Verticillium dahliae, an important asexual plant pathogen, and we report its pleiotropic involvement in fungal growth, physiology, stress response, and pathogenicity. Alternative splicing of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
(172 reference statements)
1
14
0
Order By: Relevance
“…Translocation of nuclei through septae in CATs was never observed, indicating that those CATs that develop a septum experience a translocation-competent phase of limited duration, which is completed with the septum formation. These findings are in agreement with our previous observations of nuclear migration through septal pores being extremely rare in V. dahliae (Vangalis et al 2020).…”
Section: Cat-mediated Dikaryon Formation and Nuclear Migrationsupporting
confidence: 94%
See 3 more Smart Citations
“…Translocation of nuclei through septae in CATs was never observed, indicating that those CATs that develop a septum experience a translocation-competent phase of limited duration, which is completed with the septum formation. These findings are in agreement with our previous observations of nuclear migration through septal pores being extremely rare in V. dahliae (Vangalis et al 2020).…”
Section: Cat-mediated Dikaryon Formation and Nuclear Migrationsupporting
confidence: 94%
“…These are triggered by genetic differences of the two nuclei and would typically result either in the prevention of fusion or in the destruction of the heterokaryotic cell (Gonçalves and Glass 2020). It is possible that in fungi such as V. dahliae, which almost exclusively have one nucleus per cellular compartment and nuclei cannot normally migrate through septal pores (Vangalis et al 2020), the observed degradation of the additional nucleus in the dikaryon might be the result of a homeostatic mechanism, possibly involving autophagy (Corral-Ramos et al 2015), that strictly regulates the number of nuclei per cell. In any case, however, one can speculate that even if nuclear degradation is a general phenomenon, the co-existence of nuclei for up to several hours before the onset of degradation, and the presence of chromatin of the degraded nucleus in the cell after nuclear disorganization provide possible windows of opportunity for genetic interactions of the two nuclei, as has been previously discussed (He et al 1998;Richards et al 2011;Vlaardingerbroek et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently described the strategy that we used for knocking out the V. dahliae homologs of noxA and yap1 [23]. Briefly, both mutants were constructed in the background of V. dahliae wild-type strain 123V via double homologous recombination following Agrobacterium tumefaciens -mediated transformation (ATMT) [47]. Using this method, we recently performed and described deletion of noxA and validation of the mutant strain [23].…”
Section: Methodsmentioning
confidence: 99%